Beginning windows phone 7 application development : building windows phone applications using silverlight and xna - Lecrenski, Nick C.; Watson, Karli; Fonseca-Ensor, Robert (Indianapolis, IN : Wiley Pubishing, Inc., 2011)
Provides information on designing and implementing applications for Windows Phone 7 using Silverlight and XNA.
'Wrox programmer to programmer'--Cover.
Includes index.
Keywords: Windows phone (Computer file).; Smartphones -- Programming; Application software -- Development; Mobile computing -- Programming